2003
DOI: 10.1099/mic.0.26509-0
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis demonstrates the absence of pulsatile hyphal growth

Abstract: Hyphal tip growth has been previously reported as pulsatile, defined as regularly alternating fast and slow rates of extension. The growth of pollen tubes, and hyphae of Neurospora crassa and Saprolegnia ferax were analysed using high spatial and temporal resolution. By using long (100-500 s) records of growth rate, sampled every second, it was possible to apply rigorous statistical analysis of the time series. As previously demonstrated, pollen tubes can show pulsatile growth, detectable with this system. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…While this has been confirmed for different species of pollen tubes by independent groups (Pierson et al, 1996;Messerli and Robinson, 1997;Watahiki et al, 2004;Hwang et al, 2005), it has not been repeated for tip growth in fungal hyphae (LopezFranco et al, 1994;Sampson et al, 2003). Oscillating growth in root hairs has only recently been reported (Monshausen et al, 2007) and is under further investigation in this report.…”
mentioning
confidence: 75%
“…While this has been confirmed for different species of pollen tubes by independent groups (Pierson et al, 1996;Messerli and Robinson, 1997;Watahiki et al, 2004;Hwang et al, 2005), it has not been repeated for tip growth in fungal hyphae (LopezFranco et al, 1994;Sampson et al, 2003). Oscillating growth in root hairs has only recently been reported (Monshausen et al, 2007) and is under further investigation in this report.…”
mentioning
confidence: 75%
“…Hyphal growth-rate variability Growth rates in many species vary over periods as short as 1-5 s (López-Franco et al 1994;Sampson et al 2003), related in part to dynamic cytoplasmic ion gradients (Torralba and Heath 2000); likely, there are multiple feedback loops. The erratic growth-rate variation we observed for untreated cells over 15-to 30-s intervals is consistent with previous reports, and as with Sampson et al (2003), we found that growth rate varied between hyphae as well as over time.…”
Section: Discussionmentioning
confidence: 99%
“…d Effect of taxol dissolved in 0.25% DMSO. Taxol significantly increased growth rate but not microtubule index compared with DMSO, and substantially more cells in the taxol-treated population were growing than in the control Hyphal growth-rate variability Hyphal growth rates vary over short time intervals (López-Franco et al 1994;Sampson et al 2003), although the underlying mechanism(s) are not fully understood. In N. crassa, growth-rate variations are temporally correlated with de novo generation and fusion of satellite Spitzenkörper (López-Franco et al 1995), but this phenomenon has not been reported for A. nidulans.…”
Section: Cytoplasmic Microtubules In Aspergillus Nidulans Hyphaementioning
confidence: 98%
See 1 more Smart Citation
“…regular slow-fast tip growth was first observed some time ago, (see Lopez-Franco et al, 1994). Recently, experimental evidence has been presented that suggests the variation in tip growth rate is random (see Sampson et al, 2003). Certainly, the tip growth mechanism included in our model produces a random "move/do not move" event at each time step and as such produces a random variation in hyphal tip extension rate.…”
Section: Tip Movement and Hyphal Creationmentioning
confidence: 88%